Fundamentals of Power Electronics - Reddy S. Rama (Alpha Science International, 2000)
The present book with simple treatment is the outcome of my many years of teaching. It will serve as an ideal textbook for courses on Power electronics and industrial electronics at polytechnic and undergraduate levels. It will also be very usedful to students preparing for professional courses like A.M.I.E and A.M.I.T.E.